Plataformas sociales educativas para la asignatura de ingles del tercer año de bachillerato, seccion diurna del colegio de bachillerato “primero de mayo” del canton Yantzaza, año lectivo 2014-2015 - Ordoñez Lapo, Diego Alejandro (2016)
This research is titled, SOCIAL PLATFORMS FOR LEARNING ENGLISH COURSE FOR THE THIRD YEAR OF HIGH SCHOOL, COLLEGE SECTION DAYTIME HIGH SCHOOL “FIRST OF MAY” OF YANTZAZA CITY, SCHOOL YEAR 2014-2015 is structured and developed in accordance with the Regulations of Academic Board of the National University of Loja. The central problem of the research was: indentificar WITH IMPROVED TECHNOLOGY RESOURCES AS SERIOUS (Edmodo) AND ITS INFLUENCE IN THE LEARNING PROCESS THE MATTER OF ENGLISH STUDENTS OF THE THIRD YEAR OF HIGH SCHOOL, COLLEGE HIGH SCHOOL “FIRST OF MAY” OF YANTZAZA CITY. The investigation focuses its overall goal: Develop an Educational Social Platform for improved prosecuted teaching and learning for English course students of the third year of high school, daytime section of sixth form college " First of May " school year 2014- 2015. The methods used in the research were: scientific , direct , descriptive, inductive, deductive techniques and instruments used were observation: The survey was applied to students of the Third Year High School to identify advantages and disadvantages in their learning process teaching in the subject of English. Applied the survey to identify the advantages and disadvantages in their teaching process and students receive high school third year of reference is taken Question 1 ¿Does any technology resource teacher uses to teach the subject in English? 71 students corresponding 45 % said they never used a technological resource. Clearly the lack of use of available technologies belonging Baccalaureate school “First of May” as to the question 3 considers the use of the internet for learning English? 88 students corresponding to 56 % consider the internet very important for learning English. It is noteworthy that the student by new techniques and learning platforms is more interested through the internet.